Management of Physiotherapy in Case of Brachialgia Due to Cervical Spondyloarthrosis - Ingurah Gede Verar Fujastawan (Science Midwifery, 2022)
This patient complains of pain in the neck and radiates to the shoulder, the possibility of abnormalities in the brachial plexus, the disorder can be caused by a narrowing of the foramen causing compression or it can also be caused by a tumor pressing on the nerve. Lesions on the vertebrae have different effects. Depends on the degree of which segment is affected. In the assessment of physiotherapy, the examination process to determine the patient's problems begins with anamnesis, examination, and continues with determining the diagnosis of physiotherapy. Anamnesis is divided into two, namely general history and specific history. Cervical spondyloarthrosis is a condition of the degeneration of the intervertebral discs and the connective tissue of the joints between the vertebrae. Degeneration causes the disc to begin to thin because its ability to absorb water is reduced, resulting in a decrease in the water content and the matrix in the disc decreases. Degeneration that occurs in the disc causes the disc function as a shock absorber to disappear then osteophytes will arise which causes pressure on the roots, spinal cord and ligaments which in turn causes pain and causes decreased mobility.